METHODOLOGICAL PRINCIPLES OF GEOPHYSICAL STUDIES OF KARST DANGEROUS TERRITORIES - Vyzhva, S.; Onyshchuk, V.; Onyshchuk І.; Reva, M.; Shabatura, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article is devoted to the analysis of the methodological principles of applying geophysical research methods in the study of karst-hazardous territories. The tasks that are posed in specialized studies of karst and geophysical methods for their solution are given. Four stages of specialized studies of karst-hazardous territories are identified: reconnaissance-methodological, prospecting, reconnaissance and monitoring. The set of geophysical methods for the development of these stages are determined. It is noted that a rational set of geophysical methods in the study of karst processes is determined for each individual natural environment (individual site). The possibility of performing field research by a separate geophysical method in this area, the presence of differentiation in rocks according to their physical properties which are used by a specific geophysical method and economic efficiency of the application of this geophysical method were taken into account. As an example, some results of geophysical studies carried out in the framework of the Lyubensky field of native sulfur are given.